Economy of labor in the kitchen - Corbett, Florence Ruth (My University, 1895)
Introduction: In these days we read that the whole civilized world is going “crazy” over cooking and things pertaining to the Kitchen; and, we find those everywhere who protest against this apparent extreme to which we have gone, as much as they condemned the other extreme not long past, in which comparatively no thought was given to the Kitchen.
Citation: Corbett, Florence Ruth. Economy of labor in the kitchen. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Cooking; The kitchen; Economy of labor; Theses; Manuscripts (documents)